Dehydrogenation reactions of mechanically activated alkali metal hydrides with CO2 at room temperature. (8th March 2018) - Zhao, Juan; Dong, Bao-Xia; Teng, Yun-Lei; Wang, Lu; Ping, Chao; Li, Zong-Wei
Abstract: Reactions between alkali metal hydrides MH (M = Li, Na, or K) and carbon dioxide (CO2 ) at room temperature were systematically investigated for the first time. It was found that the raw alkali metal hydrides did not react with CO2 under static-pressure conditions at room temperature, but the mechanically activated alkali metal hydrides reacted with CO2 and released large amounts of hydrogen (H2 ). Under the same ball-milling conditions, the order of reactivity of the alkali metal hydrides with CO2 was KH > NaH > LiH. The particle size of the activated alkali metal hydrides had a large influence on the reactivity of the alkali metal hydrides with CO2 . During the reactions, CO2 was reduced by alkali metal hydrides, generating elemental carbon, alkali metal oxides and H2, and it was consumed by alkali metal oxides, forming carbonates. Graphical abstract: Highlights: The reaction of MH (M = Li, Na, or K) with CO2 at room temperature was investigated. The activated MH can react with CO2 releasing large amount of H2 at room temperature. The order of reactivity of the alkali metal hydrides with CO2 was KH > NaH > LiH. The particle size has a large influence on the reactivity of the alkali metal hydrides with CO2 .